Pengajuan Kasasi Penuntut Umum Atas Alasan Ketidakcermatan Penilaian Hakim Terhadap Fakta Hukum Di Persidangan Perkara Penggelapan Dalam Jabatan - Bimo Adhi Nugroho (Verstek, 2017)
The Purpose of this research is to understand Prosecutor’s appeal in cassation on the grounds of judge’s misinterpretation in office embezzlement case (Study Of the decision of the Supreme Court Number: 413 K/Pid./2013).      This criminal act “embezzlement case” happened when the defendant be officer in PT. Sejahtera Agro Perkasa at Ancol VII/3 Ancol Barat Street, North Jakarta. The Defedant embezzle company money which trusted to him dan used for online soccer gambling. then  the judges of north Jakarta district court  release The Defedant from all lawsuits because the judge’s opinion,  this case confirm in private law case.      For this crimal act “office embezzlement” and this verdict from judge’s of north Jakarta Court district,Public Presecutor submit cassation legal effort and refer article 253 of criminal procedure code. In other side The Supreme Court considering law which used for check and decide the law to finish this case based in legitimate and reason manners, in grant cassation legal recourse from public prosecutor based on criminal procedure code.     Keywords: Legal Recourse, Cassation, and office embezzlement